Economics of Fishing Units in the Backwaters of Kerala - S., Maria Siluvai Raj; C., Hridayanathan; M., Shahul Hameed (Fishery Technology, 2025)
The cost benefit analysis of crafts and gears used for stake net, cast net, gill net, bag net and ring net operations in Vembanad lake, Kerala are presented. The rates of returns for capital employed were 67.94% for stake net, 83.17% for cast net, 64.34% for gill net, 5.32% for bag net and 20.78% for ring net. In spite of high rate of return, net income of fishing units were low.